How to Improve Dietary Practices of 19–30yo Egyptian Women Living in Urban Areas? An Optifood Analysis (OR25-04-19). (13th June 2019) - Brouzes, Chloé; Tomé, Daniel; Darcel, Nicolas; Ferguson, Elaine; Lluch, Anne
Abstract: Objectives: The double burden of malnutrition is rising in several Arab countries due to rapid changes in dietary patterns and lifestyle. Egyptian women have one of the highest BMI worldwide, and nearly one quarter of them suffer from anemia. The objective was to identify changes needed in dietary practices and product offer, which could help to rebalance nutrient intakes for women living in urban Egypt. Methods: Food intakes were obtained from a 4-days dietary record in 127 women (19–30 yo) and food prices were collected in modern and in traditional trades. Modeling analyses (Optifood software) were used to identify problem nutrients and design affordable food-based recommendations (FBRs): we assessed whether locally and consumed foods could theoretically be combined to ensure nutrient adequacy, at a fixed cost, without exceeding recommendations in energy and SFAs, total sugars and sodium. Fortified foods were included in additional modeling analyses to test their potential to improve intakes of the most problematic micronutrient to cover. Results: Preliminary results from modeling analyses indicated that iron is the most problematic recommendation to cover from a combination of local and consumed foods. Daily consumption of fruits, vegetables, grains, milk or yoghurt, and tahini associated with smart food choices in the meat-fish-eggs category would result in a low percentage of women at risk for 11 out of 12 micronutrients modeled. Among the fortified foods tested, iron fortified bread, rice, milk and yoghurt would be promising vectors to improve iron intakes. Conclusions: Local foods can ensure nutrient adequacy of most nutrients. However, strategies are needed to promote acceptable FBRs to rebalance the diet of Egyptian women. Iron fortified products could help to improve iron intakes for this population at risk of anemia. Funding Sources: Danone Research.